Petrography, geochemistry and mica mineral chemistry of granites and granophyres from the mutue fides-stavoren tin field, the Lebowa granite suite - Ray, Michael Eden (My University, 2021)
The Mutue Fides-Stavoren Tin Field in the Palaeoproterozoic Bushveld Complex, lies approximately 30 km northwest of Marble Hall in Mpumalanga. The lithologies comprise granites from the upper portions of the Lebowa Granite Suite, granophyres from the Rashoop Granophyre Suite and quartzites from the Pretoria Group of the Transvaal Supergroup. The granites are characterised by localised zones of endo- and exogranitic cassiterite mineralisation. Although these tin deposits have been mined, mainly artisanally since the early 1900s, there is limited data on the petrology and geochemistry of the granite suite of the area and no mineral chemistry. This study provides petrographic and geochemical data from samples of outcrop, half-core, and mine-dump material of the granites and granophyres and presents mica and chlorite mineral composition data for the first time from this area. Geochemically the granites can be distinguished from other granite facies of the Lebowa Granite Suite and a new name - the Gaasterland Granite - has been proposed for this granite facies. This distinction is most clearly shown by their LILE compositions (5-40ppm Sr, 350-770ppm Ba and 220-410ppm Rb) in contrast to the Nebo Granite (30-140ppm Sr, 500-2500ppm Ba and 125-250ppm Rb). The petrographic and geochemical evidence suggests that the granophyres, which are host to significant cassiterite mineralisation, formed as an early intrusive phase. This contrasts with previous interpretations that the granophyres formed either as a result of metamorphism of Transvaal sedimentary rocks during the intrusion of the underlying Rustenburg Layered Suite or as a late phase intrusion between the Lebowa Granite Suite and Transvaal sedimentary succession. A sequence of late-stage hydrothermal alteration processes was identified in the granites and granophyres. Early pervasive microclinisation of perthitic III feldspars was followed by minor albitisation in which a ‘snowball texture’ was developed. Subsequent greisenisation of the granite resulted in an assemblage of intensely sericitised alkali-feldspar, white mica, quartz and interstitial purple fluorite. Greisen halos around veins in the granophyre consist of dark green to honey brown mica, quartz, white and purple fluorite, topaz, chalcopyrite, pyrite and hematite. Cassiterite crystallised during the greisenisation and late silicification stages of alteration with a final stage of chloritisation. Mineral compositional data revealed there is a clear distinction between magmatic and hydrothermal mica compositions within the Lebowa Granite Suite. During differentiation magmatic mica evolved from an Fe-Ti-rich annite upwards through the granite sheet to hydrothermal phengite micas that are depleted in Fe and enriched in Al. A late stage hydrothermal annite-siderophyllite within the Stavoren Granophyre is highly depleted in TiO2 and enriched in Cl and FeO (38.0 - 41.0 wt%). Such evolved mica compositions within the roof portion of the Lebowa Granite Suite is indicative of hydrothermal alteration and tin mineralisation. Such mineralised sectors are limited in the Lebowa Granite Suite because the sheeted architecture of the intrusions limited the potential for concentration of hydrothermal fluids in apical portions thus restricting extensive rock-fluid interaction and consequent ore deposition.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Geology to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2021
Keywords: SDG-15: Life on land